Zmiany w handlu artykułami rolno-spożywczymi po przystąpieniu Polski do Unii Europejskiej - Kacperska, Elżbieta M. (Changes in Farm and Food Articles Trade after the Accession of Poland to the European Union, 2005)
The integration of Poland and the European Union caused a number of changes relating to farm and food articles trade. Poland took the European Union law in the scope of domestic trade and was included in the common customs tariff and in the common market, taking common trade policy. The rules of sale in the farm and food articles trade in the Union changed. They were connected with abolishment of the internal borders of the member countries. As the customs for farm and food articles trade were abolished, the products can be freely moved within the European Union territory, their sale market increased but at the same time - new competitiveness and quality requirements appeared. Moreover, some changes in trade documentation system, registration and taxes (VAT) occurred. Furthermore changes in farm and food articles trade with the third countries appeared. Poland took EU system of customs preferences, what caused increase of countries authorized to preferable access to Polish market as well as increase of amount of products with lower customs tariffs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 377-383